TRANSLATION TECHNIQUES APPLIED TO TRANSLATE PREMODIFIED NOUN PHRASES IN â€œLALITAVISTARAâ€ - Dian Purnama Dewi, Ni Putu (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2015)
According to Baker (1992), there are a number of translation issues that brings specific level of difficulties for the translator. Those issues includes: cultural-specific concepts, the source-language concept is not lexicalized in the target language, the source-language word is semantically complex, the source and target languages make different distinctions in meaning, the target language lacks a superordinate, the target language lacks a specific term, differences in physical or interpersonal perspective, differences in expressive meaning, differences in form, differences in frequency and purpose of using specific forms, and the use of loan words in the source text. When a translator should translate a text, the translator has to choose what should be kept and what should be sacrificed. Concerning to the issue of form difference in translation, this study is aimed at discussing about premodified NP translation and its translation problem, specifically in historical-cultural text. This aim is fulfilled by analyzing the premodified NP in a bilingual historical book written by Leber (2011) entitled ?Lalitavistara?.Result of this study shows that types of premodified English NP found in bilingual book ?Lalitavistara? which are premodified in term of adjective are varied. The English NP can take single premodification or multiple premodification by combining the adjectives with other types of premodifier. The meaning of these NPs can only be analyzed in term of grammatical equivalence. Literal translation is the most common technique used in this bilingual book Menurut Baker (1992), ada sejumlah isu penerjemahan yang membawa ktingkat kesulitan tersendiri bagi penerjemahnya. Isu-isu tersebut meliputi: konsep-konsep bahasa yang sangat terkait dengan kebudayaan, konsep dalam bahasa sumber yang tidak memiliki padanan dalam bahasa target, kompleksitas kata dalam bahasa sumber, adanya perbedaan makna pada bahasa sumber dan bahasa target, dalam bahasa target tidak ada istilah yang lebih umum, bahasa target tidak ada istilah yang lebih spesifik, perbedaan dalam perspektif fisik atau interpersonal, perbedaan dalam makna ekspresi, perbedaan struktur, perbedaan frekuensi dan tujuan dalam menggunakan struktur tertentu, dan pemakaian kata pinjaman dalam bahasa sumber. Ketika seorang penerjemah harus menerjemahkan sebuah teks, penerjemah tersebut harus memilih aspek mana saja yang harus dipertahankan dan yang mana yang harus dikorbankan. Menanggapi isu penerjemahan yang terjadi, terutama dari segi struktur bahasa, studi ini dimaksudkan untuk membahas tentang penerjemahan frase kata benda dengan premodifier dan masalah penerjemahannya, terutama dalam teks terkait sejarah dan budaya. Tujuan ini dapat dicapat dengan menganalisis frase kata benda dengan premodifier dalam buku bilingual yang ditulis oleh Leber (2011) berjudul ?Lalitavistara?. Hasil srudi ini menunjukkan bahwa jenis frase kata benda yang ditemukan dalam buku ?Lalitavistara? yang dimodifikasi dengan kata sifat beragam. Frase kata benda bahasa Inggris dapat ditemukan dengan memiliki satu premodifier atau banyak premodifier. Makna dalam frase-frase ini hanya bisa dianalisis dari segi ekuivalensi gramatikal saja. Teknik penerjemahan literal yang paling banyak dipakai dalam menerjemahkan buku bilingual ini.